The Netherlands in a Nutshell: Highlights from Dutch History and Culture (2009)
Many think they know the legends behind tulipmania and the legacy of the Dutch East India Company, but what basic knowledge of Dutch history should be passed on to future generations? This overview of historical highlights, assembled by a number of specialists in consultation with the Dutch general public, provides a thought-provoking and timely answer. The democratic process behind the volume is reminiscent of the way in which the Netherlands has excelled for centuries at collective craftsmanship, and says as much about the Netherlands as does the outcome of the opinions voiced. The Netherlands in a Nutshell offers a mine of information for visitors to the Netherlands, and should appeal to anyone interested in the history of this fascinating and multi-faceted land in the heart of Europe.